The Role of Probiotics and Prebiotics in the Prevention and Treatment of Obesity - Cerdó, Tomás; García-Santos, José; G. Bermúdez, Mercedes; Campoy, Cristina (Nutrients, 2019)
Obesity is a global pandemic complex to treat due to its multifactorial pathogenesis—an unhealthy lifestyle, neuronal and hormonal mechanisms, and genetic and epigenetic factors are involved. Scientific evidence supports the idea that obesity and metabolic consequences are strongly related to changes in both the function and composition of gut microbiota, which exert an essential role in modulating energy metabolism. Modifications of gut microbiota composition have been associated with variations in body weight and body mass index. Lifestyle modifications remain as primary therapy for obesity and related metabolic disorders. New therapeutic strategies to treat/prevent obesity have been proposed, based on pre- and/or probiotic modulation of gut microbiota to mimic that found in healthy non-obese subjects. Based on human and animal studies, this review aimed to discuss mechanisms through which gut microbiota could act as a key modifier of obesity and related metabolic complications. Evidence from animal studies and human clinical trials suggesting potential beneficial effects of prebiotic and various probiotic strains on those physical, biochemical, and metabolic parameters related to obesity is presented. As a conclusion, a deeper knowledge about pre-/probiotic mechanisms of action, in combination with adequately powered, randomized controlled follow-up studies, will facilitate the clinical application and development of personalized healthcare strategies.